P-type ATPases in Health and Disease - Sigrid A. Langhans (Frontiers Research Topics, 2019)
P-type ATPases are a large group of evolutionary related ion and lipid pumps that have in common that they catalyze a transient phosphorylated intermediate at a key conserved aspartate residue within the pump in order to function. While all the P-type ATPases perform active transport across cellular membranes, they have different transport specificities and serve diverse physiological functions. The ion pumps of the P-type ATPase family create electrochemical gradients that are essential for transepithelial transport, nutrient uptake and membrane potential. They mediate cellular signaling and provide the ligands for metalloenzymes. Phospholipid flippases, also members of the P-type ATPase superfamily, regulate the asymmetric lipid distribution across the lipid bilayer and are critical for the biogenesis of cell membranes. Since all of these ATPases serve fundamental cellular functions, malfunctioning is associated with various pathophysiological processes and dysfunctions of P-type ATPases are known to contribute to cardiovascular, neurological, renal and metabolic diseases. However, with the ever growing knowledge about the diseases associated with the malfunction of P-type ATPases, they are also promising targets for future drug development. In eukaryotes the most prominent examples of P-type ATPases are the Na+,K+-ATPase (sodium pump), the H+-ATPase (proton pump), the H+,K+-ATPase (proton-potassium pump) and the Ca2+-ATPases (calcium pumps). Mutations in the alpha2 and alpha3 subunit of Na,K-ATPase have been associated with neurological diseases, including rapid-onset dystonia-parkinsonism, familial hemiplegic migraine and alternating hemiplegia of childhood. Dysregulation and loss of expression of Na,K-ATPase and plasma membrane Ca-ATPases may be involved in cancer progression. Malfunctioning of the Ca-ATPases is also thought to contribute to hypertension and neurodegenerative diseases and mutations can cause cardiac dysfunction, deafness, hypertension and cerebellar ataxia. Mutations in the SERCA calcium pumps can cause heart failure, Brody myopathy and Darier disease and mutations in the Cu-ATPase genes cause Menkes and Wilson disease. Deficiencies in phospholipid flippases have been linked to progressive familial intrahepatic cholestasis, obesity, diabetes, hearing loss and neurological diseases.